2023
DOI: 10.1177/20552076231171510
|View full text |Cite
|
Sign up to set email alerts
|

Screen time, phone usage, and social media usage: Before and during the COVID-19 pandemic

Abstract: Objective Technology use has increased in the past several years, especially among younger generations. The COVID-19 pandemic drastically changed how people work, learn, and interact, with many utilizing technology for daily tasks and socializing. Methods The current study investigated a sample of college students using a cross-sectional design to determine whether there was a change in how much time students spent on screens, phones, and social media. Results Findings indicated that time on screens and phones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Undoubtedly, smartphones can offer millennials access to creating new opportunities for self-expression, exploration and creativity (Erdem and Uzun, 2022;Sfeir et al, 2023). Furthermore, past studies have shown that smartphones offer a platform for self-expression, for instance, via social media, that encourages selfactualisation and personal growth connected to openness (Livingstone, 2008;Talbot and Briggs, 2022;Voss et al, 2023). As such, an increase in openness to experience will likely increase millennials' habitual smartphone use as they seek out and embrace these opportunities provided by their devices (Tovar et al, 2023).…”
Section: The Five-factor Modelmentioning
confidence: 99%
“…Undoubtedly, smartphones can offer millennials access to creating new opportunities for self-expression, exploration and creativity (Erdem and Uzun, 2022;Sfeir et al, 2023). Furthermore, past studies have shown that smartphones offer a platform for self-expression, for instance, via social media, that encourages selfactualisation and personal growth connected to openness (Livingstone, 2008;Talbot and Briggs, 2022;Voss et al, 2023). As such, an increase in openness to experience will likely increase millennials' habitual smartphone use as they seek out and embrace these opportunities provided by their devices (Tovar et al, 2023).…”
Section: The Five-factor Modelmentioning
confidence: 99%
“…During the lockdown and social distancing measures implemented amidst the coronavirus disease 2019 (COVID-19) pandemic, the utilization of DDCI, such as smartphones, desktop computers, laptops, and tablets, increased due to the popularization of remote work, education, entertainment, and social interaction [ 15 , 16 ]. Particularly, Peru declared a state of emergency in March 2020, leading to the implementation of social distancing measures, including quarantine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transition from high school requires that students, who are already navigating myriad psychological changes during mid-to late-adolescence [2], adapt to unfamiliar academic and social environments while coping with newfound independence and novel living arrangements [3]. The widespread adoption of virtual instruction since the onset of the COVID-19 pandemic has created new barriers to connecting and increased students' screen time, which is associated with depression, anxiety, and stress [4,5]. These factors, coupled with increased sedentary time [6], pressure to succeed, and stress related to academic performance and post-graduation plans [7], contribute to the poor mental health of many undergraduates.…”
Section: Introductionmentioning
confidence: 99%